Influence of bend geometry on flow accelerated corrosion under neutral pH conditions. (April 2021) - Madasamy, P.; Mukunthan, M.; Chandramohan, P.; Krishna Mohan, T.V.; Sylvanus, Andrews; Natarajan, E.; Rani, H.P.; Velmurugan, S.; Rangarajan, S.
Highlights: Geometric effect of feeder pipe on the flow accelerated corrosion was studied. Based on geometric effect studies the accelerated corrosion areas were identified. Using experimental data based CFD simulation identified vulnerable critical locations. Abstract: Flow accelerated corrosion (FAC) is an unavoidable problem in the integral part of the pipe line systems of Nuclear Power Plants worldwide. This has a significant influence on the thickness loss of the pipe line which affects the operation and maintenance of the plants. During the prolonged operation of the plants, FAC leads to inside wall thinning, rupture and catastrophic failure of the pipeline systems and ultimate shutdown of the reactor system for maintenance. Qualitative coupon based chemical off-line analysis techniques were only followed earlier for the prevention of untoward incidents. With the introduction of ultrasonic nondestructive thickness measurements viz., pre-service, in-service and inspection during shutdowns, the possibility of accidents have been reduced to a maximum extent. However, detailed understanding of FAC and wall thinning of pipes due to different plant operation conditions such as flow velocity, different pH, different temperature and pressure values etc., are not available even today. The present experimental study is aimed to throw light on the parameters that have more impact on FAC. Also it is aimed to identify the vulnerable locations and wall thickness loss along the clock positions. The output of this study will gain currency while dealing with FAC code, and plays a critical role in the establishment of safe and reliable and continuous plant operations. According to existing literature, one of the most important parameters that affect FAC is the piping configuration i.e., geometry of flow path. Hence, the present study is aimed towards the understanding of FAC with respect to the bend angle and bend radius of the carbon steel piping. In this study, carbon steel pipes as per ASTM A106 Gr'B' material with two bend angles viz. 58° and 73° with bend radius 2D and 4D, where D denotes the outer diameter of the pipe, have been chosen. These parameter ranges are available in the existing reactor and hence four different pipe bend specimens have been undertaken. Therefore, the four different pipe specimen holders of ASTM A106 Gr 'B' materials having 15NB (Nominal Bore) pipe bends were designed and fabricated. Under the similar experimental conditions, using the Computational Fluid Dynamics (CFD) studies, the velocity distribution, the wall shear stress and the turbulent kinetic energy were simulated and correlated with the corresponding measured wear rate. Basic parameters like pipe material, bend angle, bend radius, etc. have been used for the simulation studies. Comparison of the simulated flow rate with the experimental values of wall thickness obtained through the ultrasonic measurements indicate that the bend angle and bend radius of the geometry play a crucial role on FAC.